RE-EXAMINING SOCIAL TRANSFORMATION IN SOUTH AFRICA: AN INQUEST INTO THE DEMOLITION OF COLONIAL AND APARTHEID STATUES - Malesela Edward Montle (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The ending of apartheid in 1994 saw the democratic society of South Africa implementing measures for social transformation. This comes after the apartheid regime had institutionalised autocratic attitudes, racial tension, political and socio-economic inequality in the country during its rule. The abolishment of apartheid policies came with a mandate to discard the remnants of imperialism and foster social transformation in South Africa. This noted, the quest for social transformation in the country escalated to a point of ravaging statues that are postulated to be of colonial and apartheid forces from 2015 headlining the renowned case of #RhodesMustFall. This qualitative study sought to explore the recipe for social transformation in South Africa through the analysis of the vandalism of colonial and apartheid statues. It has probed into the rationale for the removal of these statues and the degree of influence that they possess in the democratic period. The study has discovered controversies that involve some South Africans assuming that these statues do not deserve a place in the post-apartheid South Africa and the call for their removal being justified while others claim that this initiative is bureaucratic and not problem-solving.